KONTRIBUSI PEMUNGUTAN RETRIBUSI TERMINAL TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus pada Terminal Tirtonadi Surakarta tahun 2011 – 2015) - Gravita Sari Riska Permata Putri, Suharno & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study was to examine the effectiveness, contribution andgrowth rate Terminal Tirtonadi retribution against region income Surakarta 2011-2015. This research is a case study at Terminal Tirtonadi in Surakarta. The type ofdata used quantitative and qualitative data. Sources of data used secondary sources.The technique of collecting data used interviews, documentation and observation.Data were analyzed used the ratio of effectiveness, contribution ratio and the ratio ofthe rate of growth. The results showed effectiveness ratio levy Terminal TirtonadiSurakarta in 2011-2015 is quite effective in improving the original income forpersentese of 88,2%. Contributions levy in Terminal Tirtonadi Surakarta in 2011-2015 did not succeed in improving the original income for contribution ratio of1,64%. The growth rate of contributions retrubusi in Terminal Tirtonadi Surakartayears 2011-2015 are not successful with a ratio of 15,87%.Keywords: contributions, terminal charges, local revenue